OPTIMASI PENURUNAN NILAI BOD, COD DAN TSS LIMBAH CAIR INDUSTRI TAPIOKA MENGGUNAKAN ARANG AKTIF DARI AMPAS KOPI - Irmanto Irmanto; Suyata Suyata (Universitas Jenderal Soedirman, 2010)
Activated carbon from coffee dregs for TSS, BOD and COD removal of tapioca industrial wastewater has been developed. The research aimed to know the quality of activated carbon from dregs of coffee as adsorbent, consist of total rendemen, water content, ashes content and iodium adsorption; to know about the optimum contact time and optimum pH from activated carbon on reducing BOD, COD and TSS value from tapioca industrial wastewater and also to know about the decrease percentage of BOD, COD and TSS value using activated carbon from dregs of coffee. Activated carbon from dregs of coffee are activated using HCl 0,1 N and carbonization at 350°C in muffle furnace. Then, activated carbon was contacted with the tapioca industrial wastewater and used on decreasing BOD, COD and TSS value from tapioca industrial wastewater with contact time varieties 0, 10, 30, 60, 90 and 120 minutes and at pH varieties of wastewater 4, 5, 6, 7, 8, 9 and 10. The decreasing of BOD value was measured by Winkler method, decreasing of COD value measured by iodometric method and decreasing of TSS value measured by gravimetric method. The result of the research showed that the activated carbon produced characteristic consist of rendemen 14,55%; water content 3,4%; ashes content 1,88% and iodium adsorption 750,25 mg/g. It is indicated that the activated carbon that is got from dregs of coffee fulfill the criteria required by SNI No. 06-3730-1995. The result of research also showed that the activated carbon from dregs of coffee could be used for reducing the BOD, COD and TSS value in tapioca industrial wastewater at the optimum contact time of 30 minutes and pH 7. The optimum percentage of activated carbon from dregs of coffee in decreasing BOD value of tapioca industrial wastewater are 33,51%; COD value 78,96% and TSS value 61,05%.